LATAR KEPERCAYAAN YANG MEMPENGARUHI PERMUKIMAN DAN RUMAH TENGGER DI JAWA TIMUR - Hari Lelono (Berkala Arkeologi, 2002)
In the life of human beings, religion universally always receives special attention, especially for communities that are 'far away' from the development of civilization, for example, people who live in the mountainous area of ​​Tengger. This society upholds things related to immanent or hereditary beliefs. The exact background of this community's beliefs is not yet known, but at present the Tengger people who live in the mountainous area (Wong Gunung) have adopted religions: Hinduism, Buddhism, Islam, and Christianity. The development of these religions has not had much influence on the traditional customs and ceremonies they perform, such as kasada, karo, and entas-entas. Periodic traditional ceremonies are carried out once a year by all Tengger people together, both those who live in the mountains and below (ngare). Togetherness as a feeling of one brother (saktudara) really appears in these ritual activities regardless of the religious background adopted.